Variasi sudut pemasangan tabung kompresor terhadap unjuk kerja pompa hidram - Sutanto, R.; Wardani, K.; Alit, I.B.; Wirawan, M. (Dinamika Teknik Mesin, 2018)
Water is one of the factors which very important and necessary in the life of living creatures. Therefore,  water  must  be  available  whenever  and  wherever  in  the  quantity,  timing,  and sufficient quality. Hydraulic Ram Pump (Hydram) is a pump which does not require external energy as the power source. The purposes of this research are understanding the influence of mounting tube compressor with tilt angle from the water weight-lift of output pipe .This  research  uses  hydrant  pump  by  the  specification of  tube  compressor where  its’ diameter 3 inches and a height of 60 cm. The falling angle of pump is 35°. The falling-height is 2 meter with 4 variations of weight-lift 4, 4½, and 5 meters.The method of analysis is conducted by analyzing data obtained during the experiment, where the   results in the form of quantitative data which is presented in type of   tables and displayed in graphical form. The results of the research shows that  the best output debit on mounting tube compressor variation 90° that is 0.035 l/s  with 4 meters water weight-lift, while the lowest output debit on mounting tube compressor variation that is 0.011 l/s 5 meters water weight-lift. The best efficiency is 27.3 % in the mounting tube compressor variation 90°  with 4 meters of water weight-lift, while the lowest efficiency is 6.5 % in the mounting tube compressor variation 90° with 5 meters of water weight-lift.